Student Success in Face-To-Face and Distance Teleclass Environments: A matter of contact? - Deka, Teddi S.; McMurry, Patrick (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2006)
Learning from a distance continues to gain popularity. An influx of traditional, and even on-campus students attest to its flexibility, but are they equipped to succeed in a low-contact distance environment versus a face-to-face, on-campus environment? This research explored whether several variables including background, preparedness and self-perceptions assessed within the first week of class contributed differently to the success of students completing one-way distance teleclasses (n = 35) versus students completing the same classes in face-to-face, on-campus environments (n = 64). The distance students were less successful than face-to-face students when exam grades were examined (A, B, C versus D, F, drop). For distance learners, higher reading comprehension and scholastic competence were indicative of exam grade success. Student-initiated contact with the instructor was marginally related to distance student success. For face-to-face learners, reading comprehension, reading rate and lower athletic competence was indicative of exam grade success. Suggestions to help students decide whether distance learning is right for them and ways to support distance learners in low-contact environments are discussed.